Where are pedestrians injured and killed on Kampala city's road network? - Zziwa, Esther Bayiga; Kobusingye, Olive; Guwatudde, David (Frontiers in Sustainable Cities, 2022)
Road traffic crashes are a threat to walkers in cities in the global south. It is important for us to know where these crashes frequently occur as well as gain an in-depth understanding of the traffic generators around these sites. Kampala city has experienced many changes over time, and as a result, the crash sites could have changed over time. Pedestrian crashes in cities cluster in specific places than others on a road network known as black spots. It is important to know and update the current black spots as well as reassess the circumstances surrounding these crash sites. This study utilized 5-year traffic crash data (2015–2019) to map and categorize pedestrian black spots in Kampala city, Uganda, by road location type, as well as the nature of activity happening around. A total of 1,095 unique crash locations emerged from the data. Based on the criteria of locations with at least 10 serious or fatal crashes in 5 years, 46 locations were identified as black spots. The bulk (48%) of serious and fatal pedestrian black spots were junctions, especially those with traffic lights, while 74% of these black spots were around places with commercial land use. Whereas implementation of appropriate interventions at black spots is a general well-proven method for reducing the number and severity of crashes at these sites on the road network, the measures taken to treat accident black spots vary from place to place dependent on the unique local circumstances and risk factors. The draft black spot list serves as a basis for further investigation and analysis of the local risk factors surrounding serious and fatal pedestrian crashes in low-income settings as a key step in generating appropriate interventions.